TEACHER ROTATION FOR CIVIL SERVANTS IN SOUTH KALIMANTAN PROVINCE ROTASI GURU PEGAWAI NEGERI SIPIL DI PROVINSI KALIMANTAN SELATAN - Yasinta Ayu Sabrina Putri; Tommy Oktavianor (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
The policy of rotating Civil Servant (PNS) teachers in South Kalimantan Province was introduced to address the urgent need for a more balanced distribution of educators, especially given the disparities between urban and remote regions. This study seeks to assess both the effectiveness and the implementation of the rotation policy within the provincial government using a descriptive qualitative method and the CIPP (Context, Input, Process, Product) evaluation framework. Data collection involved in-depth interviews, observations, and document analysis, while data were analyzed using Creswell’s techniques with the aid of NVivo15 software. The findings reveal that the implementation of teacher rotation in South Kalimantan still encounters significant challenges, such as inconsistencies between Dapodik and Simpeg staffing databases, a shortage of replacement teachers particularly in remote locations and the influence of vested interests that undermine merit-based principles. Most rotation applications are driven by personal reasons, including residence and family considerations, with only a few aimed at refreshing placements. These results indicate that the objective of achieving equitable teacher distribution has not been fully realized, as ASN teachers remain concentrated in urban areas. Thus, there is a pressing need to strengthen governance, harmonize personnel data systems, and ensure more transparent oversight, so that the rotation policy can effectively promote equitable teacher distribution and enhance the quality of education across South Kalimantan.